Split-dose preparation for colonoscopy increases adenoma detection rate: a randomised controlled trial in an organised screening programme. Issue 2 (9th December 2015) - Radaelli, F; Paggi, S; Hassan, C; Senore, C; Fasoli, R; Anderloni, A; Buffoli, F; Savarese, M F; Spinzi, G; Rex, D K; Repici, A
Abstract : Objective: Although a split regimen of bowel preparation has been associated with higher levels of bowel cleansing, it is still uncertain whether it has a favourable effect on the adenoma detection rate (ADR). The present study was aimed at evaluating whether a split regimen was superior to the traditional 'full-dose, day-before' regimen in terms of ADR. Design: In a multicentre, randomised, endoscopist-blinded study, 50–69-year-old subjects undergoing first colonoscopy after positive-faecal immunochemical test within an organised colorectal cancer organised screening programmes were 1:1 randomised to receive low-volume 2-L polyethylene glycol (PEG)-ascorbate solution in a ' split-dose ' (Split-Dose Group, SDG) or ' day-before ' regimen (Day-Before Group, DBG). The primary endpoint was the proportion of subjects with at least one adenoma. Secondary endpoints were the detection rates of advanced adenomas and serrated lesions at per-patient analysis and the total number of lesions. Results: 690 subjects were included in the study. At per-patient analysis, the proportion of subjects with at least one adenoma was significantly higher in the SDG than in the DBG (183/345, 53.0% vs 141/345, 40.9%, relative risk (RR) 1.22, 95% CI 1.03 to 1.46); corresponding figures for advanced adenomas were 26.4% (91/345) versus 20.0% (69/345, RR 1.35, 95% CI 1.06 to 1.73). At per-polyp analysis, the total numbers of both adenomas and advanced adenomas per subject were significantly higher in the SDG (1.15 vs 0.8, p <0.001; 0.36 vs 0.22, p<0.001). Conclusions: In an organised screening setting, the adoption of a split regimen resulted into a higher detection rate of clinically relevant neoplastic lesions, thus improving the effectiveness of colonoscopy. Based on such evidence, the adoption of a split regimen for colonoscopy should be strongly recommended. Clinical trial registration number: NCT02178033.